Linguistic Features of English Inspirational Quotations denoting to Education - Lê Thị Thu Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is aimed at identifying and describing the linguistic nature of Inspirational English Quotations Denoting Education (IEQEs) in order to obtain an in-depth understanding of the features that characterize a specific type of text. Hence, the study may provide learners of English with a better insight of IEQEs so that they will be more interested in the linguistic features of IEQEs and apply them in their speeches or writing impressively and successfully. Furthermore, it is hoped that the significance of the research can, to some extent, inspire learners of English in their efforts to achieve goals in learnin